PREPARATION OF TEACHERS OF TECHNICALLY-ORIENTED DISCIPLINES IN THE FIELD OF EXPERIMENTAL WORK - HAVELKA, Martin; SERAFÍN, Čestmír; KROPÁČ, Jiří (Trends in education, 2012)
The contribution deals with the conditions creating a complex educational environment in the constructivist concepts such as environment, which affects the fundamental level of the competence of the educator and makes his professional prowess. For the application of progressive teaching methods is a necessary condition for self experience in the framework of activities carried out in connection with the content of education. This objective is a part of the contents of disciplinary didactics application of the subject Teaching technical and information education at lower and upper secondary schools.
Keywords: education; innovation; information and communication technology; laboratory work; technical education; the preparation of teachers; disciplinary didactics.